Cortisol responses to emotional stress in men: Association with a functional polymorphism in the 5HTR2C Gene - Brummett, Beverly H. (2011)
The serotonin 5HTR2C receptor has been shown to mediate HPA axis activation during stress. We hypothesized that a functional polymorphism (rs6318) of the 5HTR2C gene would be associated with HPA axis response to a laboratory stress protocol. The present sample consisted of 41 men (22 African Americans, 19 Caucasians). We found that at rest men with the more active rs6318 Ser23 C allele had similar cortisol values compared to those with the less active sys23 G allele. During laboratory stress, however, men with the Ser23 C allele exhibited the predicted significantly higher cortisol levels (p < .001), as well as larger increases in anger (P=0.08) and depressive mood (P=0.006) ratings, compared to the sys23 G carriers. The increase in cortisol was significantly related to the increases in ratings of anger and depression assessed before and after the emotion induction, and these correlations became nonsignificant when rs6318 genotype was covaried. We conclude that genetic variation in 5HTR2C may be associated with HPA axis activation and stimulated by emotional stress, and also with both psychological and physiological endophenotypes that increase the risk of cardiovascular disease and type 2 diabetes.